Entrainment across a density interface in a two-dimensional flume compartment - Foo, Miaw Hui. (2009)
This study investigated the entrainment characteristics across a freshwater-seawater interface induced by an underlying flow stream. Extensive experiments of the entrainment rates were carried out in two-dimensional rectangular flume compartments; in which the different geometrical and flow parameters were varied to allow their influence on the entrainment rate to be evaluated. Detailed observations of the flow patterns and entrainment mechanisms at the interface were also made.